Analisis Pengaruh Brand Image Terhadap Minat Beli Ulang Oleh – Oleh Khas Sumatera Barat (Survey Pada Masyarakat Kota Padang Panjang) - Girsang, Nitasri Murawaty; Riski, Wahyu Nova; Karyadi, FX Yatno (Asosiasi Ide Bahasa Kepri, 2024)
This research aims to determine the effect of brand image variables of Christine Hakim's sanjai balado chips product on repurchase intention on consumers in the city of Padang Panjang, West Sumatra. The type of research used is quantitative research with a descriptive approach. The respondents in this research were residents of the city of Padang Panjang who had repeatedly purchased Christine Hakim's sanjai balado chips products. The number of samples in this research was 100 people and the method used was accidental sampling. Data collection was carried out by distributing questionnaires to all respondents selected in this study. Based on the results of descriptive statistics conducted, it shows that the majority of respondents expressed their perception of agreeing with all the questionnaire statements distributed. The research results show that brand image has a positive and significant effect on repurchase interest with a significance level of 0.000.